The impact of the increasing demand for biofuels in the EU on the possibility to conduct collective action for reaching a common good: The changes in the community-based management of the common pastures in Ethiopia - Pavlina Miteva (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
The negative impact of EU biofuel policy on the agricultural markets, carbon emissions and global land use has been evidenced through many studies. Besides the often affirmed negative implications, the paper suggests that in countries targeted by land investments for biofuel production, there are further implications for the social structure of their societies i.e., for the institutionalized relationships among the individuals living in those societies. More specifically, the paper suggests that there are implications for those relationships that command the conducting of collective action for reaching a common good, such as the successful management of a common-pool resource (CPR). For this purpose, the paper chooses to focus on the community-based management of the pastures in Ethiopia. The paper analyzes the changes that the traditional institutions for pasture management in Ethiopia are experiencing by applying Elinor Ostrom's design principles, while trying to determine whether and how the increased demand for biofuels affects these changes. The paper concludes that the increased areas under biofuels, by affecting the size and functionality of the pastures, provokes the formation of clearly defined boundaries of these resources and of their appropriators and causes inconsistencies between the rules that govern this resource and the local conditions. The increased demand for biofuels also incentivises governmental actions that further threaten the rights of the pastoralists to manage their resources. The justification of the paper is to add value to EU policies that attempt to mitigate negative impacts of the biofuel policy, so the paper ends with recommendations in this direction.
Keywords: D7; F5; Q15; Q28; 330; biofuels; design principles; Ethiopia; pastures; institutions for CPR management